Comparação morfológica do ovário de rainhas e operárias de Frieseomelitta varia e Apis mellifera ao longo do desenvolvimento - Delfino, Mariana Mayumi Yamashiro (Universidade Federal de São Carlos, 2025)
The stingless bee Frieseomelitta varia and the exotic bee Apis mellifera are eusocial species in which the reproductive work is divided between two female castes with distinct morphophysiologies. Queens are responsible for the reproductive task, while workers take care of the colony maintenance. In F. varia, workers are incapable of reproduction, while workers of A. mellifera retain reproductive potential. To understand the mechanisms behind the difference in reproductive capacity of these bees, this study aimed to characterize the development of the ovaries of queens and workers of Frieseomelitta varia bees, comparing them with the development of queens and workers of Africanized bees Apis mellifera. For this purpose, an in vitro rearing protocol of F. varia queens and controlled egg-laying of A. mellifera queens were implemented to obtain specimens at the desired stages. The ovaries of queens and workers of both species were dissected and marked with fluorescent components to visualize the nuclei and actin filaments. The development time of F. varia queens was determined from the moment of transfer of newly hatched larvae, which emerge after 31.92 ± 1.03 days. Here, we also performed the morphological characterization of the ovaries of F. varia queens in the pre-defecating larval phase, white-eyed pupa and brown-eyed pupa without pigmentation and with light and dark pigmentation on the body; and of natural workers in the defecating larval phase, newly emerged and foraging adults, in addition to an intermediate adult phase between emergence and foraging. For the species A. mellifera, the following queen phases were obtained: pupa with brown pigmentation on the eyes and different intensities of body pigmentation; and natural workers in the last larval instar and in pupal stages without eye pigmentation, with brown eye pigmentation and different levels of body pigmentation, in addition to a newly emerged adult phase. Our results indicate that both species present a similar process of ovarian development in workers and queens in which the initial structure found in larvae elongates and reaches the conformation seen in adults while still in the pupal phase. The difference seems to be in the organization of the cytoskeleton of the membranes that cover the ovaries. While these membranes remain organized throughout the development of A. mellifera and F. varia queens and A. mellifera workers, they appear disorganized in F. varia adults. This work produced a catalog of images of the development of the ovaries of F. varia and A. mellifera queens and workers. In addition, we contributed with information on the reproductive biology of bees, an organism whose ecological and economic services are invaluable.
Morphological comparison of the ovary of queens and workers of Frieseomelitta varia and Apis mellifera throughout development
Keywords: Abelhas sem ferrão; Abelhas melíferas; Desenvolvimento do ovário; Morfologia; Frieseomelitta varia; Apis mellifera; CIENCIAS BIOLOGICAS